15 Prevalence of ECG arrhythmias in non-implanted, drug-naive, freely moving beagle dogs. Issue 1 (10th December 2010) - Cools, F; Janssens, S; Vanlommel, A; Teisman, A; Gallacher, D J
Abstract : The purpose of this study was to assess the normal prevalence rate of spontaneous arrhythmias in 51 drug-naive, non-implanted, freely moving Beagle dogs (10 M+41 F, CEDS, France). Non-implanted ECG assessment was done in jacketed dogs with six external leads and a T47G-encoder (PhysioJacket, ITS). Trained lab personnel visually scrutinised the full 22-h (day and night) ECG recordings and scored the incidence of different types of arrhythmias. Only one of these 51 animals showed no arrhythmias during the 22-h observation period. Based on this assessment of spontaneous ventricular arrhythmias, we judged 12 (23.5%) of these animals to be unsuitable for telemetry implantation for use in safety pharmacology studies. In conclusion, thorough evaluation of ECG morphology of naïve Beagle dogs before implantation of telemetry instruments will improve conscious telemetered-dog arrhythmia studies.